Perdarahan Intraserebral - Basli Muhammad; Jihan Nabila (Jurnal Ilmu Kesehatan dan Gizi, 2023)
Haemorrhagic stroke, or also known as spontaneous intracerebral haemorrhage (PIS), is one of the pathological types of stroke caused by intracerebral blood vessels. This condition causes neurological symptoms that occur suddenly and often followed by symptoms due to the spatial effects or increased intracranial pressure (TIK). Generally speaking, the number of strokes is increasing, according to (RISKESDAS) the Ministry of Health of the Republic of Indonesia there is an increase in stroke prevalence from 8.3 (2007) to 12.2 (2013) per 1000 people. In PIS, primary injury occurs: neuron and glia damage mechanically followed by deformation, neurotransmitter release, mitochondrial dysfunction and cell membrane depolarization. Secondary injuries due to haemoglobin breakdown and coagulation factors especially thrombin. The product will activate microglia so it produces toxic substances such as reactive oxygen species (ROS), matrix metalloproteinase (MMP), cyclooxygenase-2, prostaglandin, heme oxygenase-1 (HO-1), complement factor, tumour necrotizing factor α (TNF α), and interleukin 1β causing network injury. In addition to injury, there's also a replacement of dead cells through the neurogenesis process, which is the growth of neuronal stem cells in the subventricular and hippocampus areas. The number of hemorrhagic strokes in Asia is higher than in the West. This could be due to the high incidence of hypertension in the Asian population.